Factors affecting clinical decision-making in inflammatory bowel disease and the role of point-of-care calprotectin. (17th January 2018) - Derwa, Yannick; Williams, Christopher J.M.; Sood, Ruchit; Mumtaz, Saqib; Bholah, M. Hassan; Selinger, Christian P.; Hamlin, P. John; Ford, Alexander C.; Gracie, David J.
Objectives: Patient-reported symptoms correlate poorly with mucosal inflammation. Clinical decision-making may, therefore, not be based on objective evidence of disease activity. We conducted a study to determine factors associated with clinical decision-making in a secondary care inflammatory bowel disease (IBD) population, using a cross-sectional design. Methods: Decisions to request investigations or escalate medical therapy were recorded from outpatient clinic encounters in a cohort of 276 patients with ulcerative colitis (UC) or Crohn's disease (CD). Disease activity was assessed using clinical indices, self-reported flare and faecal calprotectin ≥ 250 µg/g. Demographic, disease-related and psychological factors were assessed using validated questionnaires. Logistic regression was performed to determine the association between clinical decision-making and symptoms, mucosal inflammation and psychological comorbidity. Results: Self-reported flare was associated with requesting investigations in CD [odds ratio (OR) 5.57; 95% confidence interval (CI) 1.84–17.0] and UC (OR 10.8; 95% CI 1.8–64.3), but mucosal inflammation was not (OR 1.62; 95% CI 0.49–5.39; and OR 0.21; 95% CI 0.21–1.05, respectively). Self-reported flare (OR 7.96; 95% CI 1.84–34.4), but not mucosal inflammation (OR 1.67; 95% CI 0.46–6.13) in CD, and clinical disease activity (OR 10.36; 95% CI 2.47–43.5) and mucosal inflammation (OR 4.26; 95% CI 1.28–14.2) in UC were associated with escalation of medical therapy. Almost 60% of patients referred for investigation had no evidence of mucosal inflammation. Conclusions: Apart from escalation of medical therapy in UC, clinical decision-making was not associated with mucosal inflammation in IBD. The use of point-of-care calprotectin testing may aid clinical decision-making, improve resource allocation and reduce costs in IBD.